Psycho-pedagogical peculiarities of the creative abilities of students - Сафарян, Світлана (Educological discourse, 2013)
The article deals with the problem of forming of the creative personality of schoolchildren in the process of their teaching. The special attention is paid to some psychological and pedagogical features of the process of forming and development of creative abilities as a problem of educational system. The psychological and pedagogical sources which are devoted to researches of the problem of teaching and development of creation in the system of school education are analyzed and methodical recommendations concerning the organization of teaching and educational process, directed on forming of creative abilities of schoolchildren are given.